Soul of Zelda: A Memoir of an Ephemeral Being - Kopitch, Mitchell (My University, 2018)
Hybrid document of memoir and fiction concerning fantasy, video games, and the ways in which game design nuance can be found in every day life. Particular attention is put on The Legend of Zelda from 1986, the first 3D Zelda installment, Ocarina of Time in 1998, and Dark Souls from 2011. This is a fictional story heavily inspired by those games and many others, but the story and characters are original, including a queer/gender bending protagonist. The story-line is a creative work that emulates the underlining philosophy of fantasy video games such as Zelda and Dark Souls, re-imagining video game design and personal gaming experiences as prose.
Thesis (Master's)--University of Washington, 2018
Keywords: Aesthetics; Dark Souls; Gender bender; Queer; Video Games; Zelda; Creative writing; Multimedia communications; Aesthetics; Interdisciplinary arts and sciences